Construcción de un Intercambiador de Calor Tubular de Carcasa para el Laboratorio de la Universidad Antonio Nariño de Nieva Huila (2022)
The project consists of the design and construction of a shell and tube heat exchanger to serve in the laboratory of the Antonio Nariño University, so that it becomes a device for pedagogical use in the teaching and learning process of students of the Facu of Mechanical Engineering for testing, acquiring, practicing and confirming basic knowledge in heat transfer, fluid mechanics and thermodynamics. The design of the lty equipment was carried out in three stages: Thermal design which serves to determine the dimensions of the tubes, the number of steps and components of the equipment by means of the mechanical design. As a result, the temperature of the hot fluid was reduced by approximately 50.88°C in the theoretical part and in practice it reached a value of an exchanger of 1.2 meters in length. 52°C as outlet temperature for